Determinación de los contaminantes en fuentes móviles producto de la combustión del parque automotor a diesel en el casco urbano de la ciudad de Latacunga, parroquia San Buenaventura - Zapata Tello, María José (2017)
This investigation gives a perspective about the atmosphere pollution generated by the diesel fleet in San Buenaventura town, producing environmental problems caused by the excessive increase in the fleet. As a first step to start the project was identified the area of study by making a visit where there is greater agglomeration of vehicular traffic. It was identified that the greatest traffic is located in San Buenaventura town, in this place monitoring carried out to 125 diesel vehicles, determining the emissions of the opacity using the measurement procedure in accordance with the standards NTE INEN 2202:2000. Determination of the opacity of exhaust emissions from diesel engines using the static test. Method of free acceleration. When was obtained the research data, a data base was realized which are tabulated and compared with the NTE INEN 2207: 2002 standards. Allowable limits of emissions produced by mobile sources of diesel. This research project is considered a field investigation, because of the obtained information was carried out with the help of the AVL DITEST gas 1000 adding the opacimeter 480 DISMOKE BT which measures the opacity in percentage (%), which was of great help to make the monitor to diesel vehicles. The information obtained allowed to know the levels of emission of gases from the exhaust of diesel vehicles toward the environment.